On regularity of linear systems with a degenerate matrix by the derivative - Symокоп V. G.; Trofimchuk, E. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
New sufficient conditions for the existence of invariant manifolds are proved for linear systems with degenerate matrix by the derivative.